RISK MANAGEMENT AND EARNINGS MANAGEMENT ON FINANCIAL PERFORMANCE IN ISLAMIC BANKING: AN EMPIRICAL STUDY OF INDONESIA - Oki Sania Riski; Rika Lidyah; Titin Hartini (Management Department, Faculty of Economics and Business, Universitas Jambi, 2022)
This study aims to determine the effect of risk management and earnings management on financial performances in Islamic banking: an empirical study of Indonesia. This study uses a quantitative research method. As for the sampling technique, we used purposive sampling. The type of data is secondary data. The samples used in this study were ten banks registered with the Financial Services Authority from 2015 to 2020. Data analysis in this study used the application of the SEM-PLS. This research indicates that risk management and earnings management affect financial performance. Keywords: Risk Management, Earnings Management, Financial Performance.